2021
DOI: 10.3389/fimmu.2021.708184
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristic Analysis of Antibodies in Patients With COVID-19: A 13-Month Study

Abstract: There is a worldwide pandemic of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection; yet our understanding remains limited on the characteristic of antibodies, especially for dynamic long-term tracking. Sequential serum samples were collected up to 416 days post onset of symptoms (POS) from 102 patients who were hospitalized with coronavirus disease 2019 (COVID-19). Immunoglobulin (Ig)G, IgM, and IgA levels targeting SARS-CoV-2 spike 1 receptor-binding domain (S1-RBD), spike 2 extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…However, the titers and neutralizing activity decline rapidly within 1-6 months and, in some patients, the NAbs are completely undetectable several months after infection [15]. Surprisingly, in some convalescents, the titer and activity of the NAbs remain high and stable, respectively extensively beyond the follow-up period after recovery [16]. In this study, NAbs against SARS-CoV-2 were detected in 98.0% of study participants, 6 months after discharge from the hospital, despite individual differences in the levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the titers and neutralizing activity decline rapidly within 1-6 months and, in some patients, the NAbs are completely undetectable several months after infection [15]. Surprisingly, in some convalescents, the titer and activity of the NAbs remain high and stable, respectively extensively beyond the follow-up period after recovery [16]. In this study, NAbs against SARS-CoV-2 were detected in 98.0% of study participants, 6 months after discharge from the hospital, despite individual differences in the levels.…”
Section: Discussionmentioning
confidence: 99%
“…Data on durability of N-IgG antibodies after COVID-19 are conflicting. The group by Shi et al looked at the different dynamics of anti-SARS-CoV-2 antibodies over time [ 7 ]. After one year, most of the antibodies, including IgA and IgM antibodies against viral spike and nucleocapsid protein dropped below detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, anti-SARS-CoV-2-nucleocapsid-IgG antibodies (N-IgG) can therefore be used to identify individuals with past SARS-CoV-2 infection. Studies have shown that seroconversion for N-IgG occurs in nearly 100% of hospitalized patients one month after infection [ 7 , 8 ]. Little is known about the durability of these antibody levels, which is crucial to know for future seroprevalence studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found similar results. At 1 year (213-416 days post-symptom onset, PSO), the residual positive rate of RBD-IgM was 7.1%, whereas S2 and N-IgM were both 0% (22).…”
Section: Igmmentioning
confidence: 99%